Pengaruh Seminar Online Whatsapp terhadap Pengetahuan menjaga Kesehatan Penderita Hipertensi di Era Adaptasi Kebiasaaan Baru - Mariatul Fadilah; Pariyana Pariyana; Jason Adi Nugraha; Desi Mawarni (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
High blood pressure or hypertension is a chronic condition where blood pressure increases. Hypertension can occur for years without realizing it. In fact, even without symptoms, damage to blood vessels and the heart continues and can be detected.Online seminars are one of the health promotion methods that can be done in the era of adapting new habits in order to increase public health knowledge. This study aims to determine the effect of online seminars on public knowledge. This study used a quasi experimental pre and post test design. The sample in this study were all participants who took part in online seminars and filled out the pretest and posttest questionnaires. Univariate data analysis shows that the majority of respondents have an average age of 25.5 years, most of them are female (71.1%), the latest education is higher education (53.9%), students (67.2%), and most of them had a good level of initial knowledge about efforts to maintain health for hypertension sufferers in the era of adaptation to new habits (81%) before attending online seminars. The bivariate data analysis shows that there is an increase in knowledge about efforts to maintain health for hypertension sufferers in the era of significant new habit adaptation before and after attending online seminars with p value = 0.000 (p value <0.05). Online seminars are the right way to promote health in increasing knowledge about efforts to maintain health for people with hypertension in the era of adapting to new habits.